Potential of B/Al‐Doped Silicene Electrodes in Na/K‐Ion Batteries. Issue 7 (8th May 2018) - Zhu, Jiajie; Gandi, Appala Naidu; Schwingenschlögl, Udo
Abstract: Metal‐ion batteries are key for energy storage in both portable electronics and large‐scale applications. As the ion capacity of the widely used graphite electrodes is limited, 2D materials, in particular silicene, are considered for possible replacement. Here, the effects of B/Al doping on the ion capacity of silicene are studied and it is demonstrated that complex charge transfer leads to ultra‐high Na capacity. Low Na/K diffusion barriers open potential for fast charge and discharge. Abstract : Silicene is considered as alternative electrode material for metal‐ion batteries to overcome the limited ion capacity of widely used graphite. Here, the effects of B/Al doping on silicene are studied and it is demonstrated that complex charge transfer leads to ultra high Na capacity. Low Na/K diffusion barriers open potential for fast charge and discharge.